2018
DOI: 10.1111/jphp.12904
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the anti-inflammatory activity of Bupleurum marginatum (Apiaceae) extracts using in vitro and in vivo experiments supported by virtual screening

Abstract: Our study provides evidence for an interesting anti-inflammatory activity of B. marginatum aerial parts offering a natural anti-inflammatory agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…BIM showed considerable anti-inflammatory activity evidenced from the reduction of TNF-α, one of the relevant inflammatory markers. Flavonoids and iridoid glucosides have been regarded as anti-inflammatory agents in many medicinal plants [62,63]. Our molecular modeling study supports this assumption: The iridoid glucoside gmelinoside H showed the highest inhibition owing to the formation of three firm hydrogen bonds with Glu 107 and Lys 98 amino acid residues at the active site.…”
Section: Discussionsupporting
confidence: 78%
“…BIM showed considerable anti-inflammatory activity evidenced from the reduction of TNF-α, one of the relevant inflammatory markers. Flavonoids and iridoid glucosides have been regarded as anti-inflammatory agents in many medicinal plants [62,63]. Our molecular modeling study supports this assumption: The iridoid glucoside gmelinoside H showed the highest inhibition owing to the formation of three firm hydrogen bonds with Glu 107 and Lys 98 amino acid residues at the active site.…”
Section: Discussionsupporting
confidence: 78%
“…CHARMm force field was assigned and the binding energies were calculated using a distance dependent dielectric implicit solvation model for the selected docking poses. However, the free binding energies were calculated in kcal/mol using the following equation: [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Human pancreatic α-amylase (HPA) (PDB ID 1B2Y), human maltase glucoamylase (HMG) (PDB ID 3TOP), human aldose reductase (AR) (PDB ID 3LEN) and human PPARGamma (PPAR) (PDB ID 4EMA) co-crystallized with their lead compounds that are the tetrasaccharide acarbose for both HPA and HMG, zopolrestat for AR and rosiglitazone for PPAR were downloaded from Protein Data Bank. [20,21] Results and Discussion…”
Section: Molecular Modelling Studiesmentioning
confidence: 99%